Self-stigma and cognitive insight in individuals at ultra-high risk for psychosis - Sportel, Bouwina Esther; van Enthoven, Mirjam; van Donkersgoed, Rozanne J. M.; Kuis, Daan Jan; van de Giessen, Tara; Lysaker, Paul H.; Hasson-Ohayon, Ilanit; de Jong, Steven; Boonstra, Nynke; Pijnenborg, Gerdina H. M. (Frontiers in Psychiatry, 2023)
Background Impaired cognitive insight and increased self-stigma have been consistently reported in individuals diagnosed with schizophrenia spectrum disorders, but little is known about its presence in individuals at ultra-high risk of developing a psychosis, although self-stigma is associated with transition.to psychosis. The current study examined whether self-stigma is already present in individuals at ultra-high risk of psychosis, and whether this is associated with impaired cognitive insight. Methods 184 participants were recruited divided over three groups, namely individuals diagnosed with a schizophrenia spectrum disorder (SSD; n = 92, 34% females), individuals at ultra-high risk for psychosis (UHR; n = 43, 59% females) and general population controls (GPC; n = 49, 27% females). All participants completed assessments on demographic information (gender, age, education), and cognitive insight. In addition, participants with SSD and individuals at UHR completed a questionnaire on self-stigma. Results The level of self-stigma did not differ between individuals at UHR and individuals diagnosed with SSD. Cognitive insight also did not differ significantly between the three groups, but the subscale self-reflection differed between the three groups [F(2,184) = 4.20, p = 0.02], with the UHR and SSD groups showing more self-reflection. Pearson’s correlation analyses showed that in individuals at UHR total cognitive insight and its self-reflection subscale were significantly associated with the alienation subscale of self-stigma, and in individuals with SSD self-certainty subscale of cognitive insight was significantly associated with stereotype endorsement. Conclusion Findings show that self-stigma was already present in the UHR phase, to a similar degree as in individuals with a diagnosis of a SSD, and is thus not dependent of previous experience of having a label of SSD. Cognitive insight in individuals at UHR of psychosis appears to be intact, but individuals at UHR showed more self-reflectiveness, and individuals at risk with high cognitive insight also experience high levels of self-stigma. Overall findings from our study suggest that pre-emptive interventions targeting self-stigma, while considering cognitive insight, are needed early on in manifestation of psychotic illness, preferably already in the UHR phase.